Pentoxifylline Attenuates Transforming Growth Factor-β1-Stimulated Collagen Deposition and Elastogenesis in Human Tunica Albuginea-Derived Fibroblasts Part 1: Impact on Extracellular Matrix - Shindel, Alan W. (2010)
INTRODUCTION: Transforming growth factor-β1 (TGF-β1) has been implicated in the pathogenesis of Peyronie’s disease (PD) and also plays a role in collagen and elastin metabolism. Pentoxifylline (PTX) antagonizes the effects of TGF-β1 and has been utilized in our clinic for the management of PD. AIM: We studied the effects of TGF-β1 and PTX on collagen metabolism and elastogenesis in tunica albuginea-derived fibroblasts (TADFs). METHODS: TADFs from men with and without PD were cultured and treated with TGF-β1 and PTX as monotherapy at differing concentrations and time points. Combination treatment (TGF-β1 followed by PTX and vice versa) was also investigated. MAIN OUTCOME MEASURES: Cell proliferation assay, enzyme-linked immunosorbent assay, and immunohistochemistry were utilized to assess the impact of TGF-β1 and PTX on TADF with respect to elastin and collagen I metabolism. RESULTS: PTX inhibited fibroblast proliferation at doses of 100 μM. TGF-β1 stimulated elastogenesis and collagen I fiber deposition in TADF in a dose- and time-dependent fashion. Pretreatment with PTX dramatically attenuated TGF-β1-mediated elastogenesis and collagen fiber deposition in TADF from men with and without PD. Interestingly, production of collagen I was higher in untreated Peyronie’s tunica (PT) cells relative to normal tunica (NT) cells; furthermore, PTX attenuated collagen production to levels similar to untreated control TADF in PT cells but not in NT cells, suggesting important intrinsic differences between PT and NT cells. CONCLUSION: Both elastin and collagen are upregulated by TGF-β1 in TADF. This likely contributes to the PD phenotype. Pretreatment with PTX attenuates both collagen fiber deposition and elastogenesis in TADF exposed to TGF-β1; these effects suggest a useful role for PTX in the management of PD.